Allergic skin conditions - causes, clinical features and treatment - Hendrick M. Motswaledi (South African Family Practice)
Allergic skin conditions are caused by allergens. When an allergen is responsible for triggering an immune system response, this results in an allergic skin condition. Some of these allergens are physical agents which evoke an immune response by way of contact with the skin and some are food-stuffs and drugs taken systemically. Allergic skin conditions include urticaria and angio-oedema, allergic contact dermatitis, atopic dermatitis, hand dermatitis, photoallergic reactions and phototoxic reactions. These conditions are briefly discussed in this article.